Spectroscopic and molecular modeling studies of N-(4-(3-methyl-3-phenylcyclobutyl)-3-phenylthiazole-2(3H)-ylidene)aniline by using experimental and density functional methods - Sen, Fatih; Ekici, Oner; Dincer, Muharrem; Cukurovali, Alaaddin (Elsevier Science Bv, 2017)
In the present study, a combined experimental and computational study on molecular structure and spectroscopic characterization on the title compound has been reported. The crystal was synthesized and its molecular structure brought to light by X-ray single crystal structure determination. The spectroscopic properties of the compound were examined by FT-IR and NMR (H-1 and C-13) techniques. FT-IR spectra of the target compound in solid state were observed in the region 4000-400 cm(-1). The H-1 and C-13 NMR spectra were recorded in CDCl3 solution. The molecular geometries were those obtained from the X-ray structure determination optimized using the density functional theory (DFT/B3LYP) method with the 6-31G(d, p) and 6-31G+(d, p) basis set in ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths, bond angles and torsion angles), vibrational assignments and chemical shifts of the title compound have been calculated theoretically and compared with those of experimental data. Besides, molecular electrostatic potential (MEP), frontier molecular orbitals (FMOs), Mulliken population analysis, Thermodynamic properties and non-linear optical (NLO) properties of the title molecule were investigated by theoretical calculations. (C) 2015 The Authors. Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Cyclobutane; Thiazole; Density functional theory (DFT); Non-linear optical effects; Frontier molecular orbital analysis (FMO)